Alterations in the gut microbiota of Chinese patients following Helicobacter pylori eradication with bismuth-based quadruple therapy - Chen, Xiao-Juan; Hu, Ming-Ye; Zheng, En-Dian; Pan, Ju-Yi (Frontiers in Microbiology, 2025)
ObjectiveThe aim of this study is to investigate the changes in gut microbiota before and after Helicobacter pylori (Hp) eradication, assess the structural distribution of gut colonies in individuals infected with Hp, and examine the alterations in gut microbiota following Hp eradication.MethodsPatients diagnosed with Hp infection between June 1, 2021, and December 31, 2021, were included in the study. A total of 26 patients who underwent standard quadruple first-line therapy for Hp eradication were prospectively enrolled. Fecal samples were collected 1 day before treatment and 6 weeks after treatment. The gut microbiota was sequenced using the 16S rRNA next-generation gene sequencer to assess changes in microbiota composition ratios and diversity, before and after treatment.ResultsAmong the 26 patients with Hp infection, aged between 19 and 55 years, 18 had positive results in the 13C urea breath test, while 8 were diagnosed through gastroscopic histopathological examination. Changes in gut microbiota diversity were observed before and after Hp eradication. At 56 days post-treatment, alpha diversity changes were not significant, whereas beta diversity changes differed in the gut microbiota. Variations were also noted in the relative abundance and composition ratios of the gut microbiota at the phylum and genus levels before and after Hp eradication. Compared to the pre-eradication state, the metabolic pathways of the gut microbiota were less abundant following Hp eradication.ConclusionSignificant changes were observed in the beta diversity of the gut microbiota, the relative abundance at the phylum and genus levels, and metabolic pathways within a short period following Hp eradication.